Elegant System for Library Management using RFID - Pradeepa, D; Valarmady, R; G Rajasekar, S (International Journal of Engineering and Technology, 2018)
Radio Frequency Identification (RFID) implies a system that exchanges the data remotely, utilizing radio frequency waves. It is programmed identification innovation. This paper is about RFID based system for library management that permits quick exchange stream and will make simple to deal with the exercises like issue and return of books from the library absent much manual intercession. This system depends on RFID readers and detached RFID tags that can store the data electronically which can be perused by the RFID readers. This system will influence clients to issue to and return of books through RFID tags simple and furthermore ascertain the comparing fine connected with the timeframe the nonappearance of the book from the library.Â Â